Identity Crisis in V.S. Naipaul’s The Mimic Men - Shrestha, Ravi Kumar (Cognition, 2021)
This paper explores the identity crisis of the protagonist Ralph Singh in the novel The Mimic Men by V.S. Naipaul. With the increasing trend of migration of people in the postwar era, the immigrants who leave their lands and settle in the host lands face multiple problems such as the identity crisis. Ralph Singh who is depicted as the protagonist in the novel suffers from the trauma because of his loss of identity crisis, which gets reflected through his writing of memoirs that indicates the construction of an authentic and dignified identity for postcolonial individuals like his own. His memoirs show howhis ancestors had migrated to Isabella, a British colony in the Caribbean, a long time ago. He embraces his reality of being a colonized individual, but is reluctant to embrace his hybrid identity. He regards mimicry and hybridity as negative forces to weaken and endanger the colonized ones’ identity. In course of dealing with the identity crisis of Ralph Singh, the postcolonial theorists such as Homi K. Bhabha, Stuart Hall and Edward Said and the critics such as SamanAbdulquadir H.D., Dr S. Sophia Christinia etc. are used. Thus, this paper deals with the identity crisis of Ralph Singh which is caused by mimicry, displacement, alienation, rootlessness and hybridity.PostcolonialNovel